Efektivitas Rizobakteri untuk Menghambat Pertumbuhan Jamur Collectotrichum acutatum Penyebab Penyakit Antraknosa pada Tanaman Cabai Merah Besar (Capsicum annuum L.) - Unedo, Dion; Suprapta, Dewa Ngurah; Suniti, Ni Wayan (Agrotrop : Journal on Agriculture Science; Vol 14 No 2 (2024)DO - 10.24843/AJoAS.2024.v14.i02.p11, 2024)
The Effectiveness of Rhizobacteria to Inhibit the Growth of the Fungus Colletotrichum acutatum that Causes Anthracnose Disease on chili pepper ( Capsicum annum L.). Anthracnose in chili pepper caused by the fungus Colletotrichum acutatum is one of the main diseases that affect the production of chili pepper. The use of rhizobacteria as biological agents is considered effective to suppress the spread of anthracnose disease in chili pepper. This study tested the rhizobacteria isolated from the rhizosphere of Graminae and citrus plants to inhibit the growth of the fungus C. acutatum in vitro on PDA media and in vivo on chili peppers. The purpose of this study was to obtain rhizobacteria that could inhibit the growth of fungus C. acutatum , both on PDA media and on chili fruit. The test results showed that the rhizobacteria isolate Yj (isolated from the rhizosphere of citrus plants) could inhibit the growth of the fungus C. acutatum on PDA media by 87.16% compared to the control. In vivo test on chili fruit showed that rhizobacteria isolate Yj could inhibit the growth of C.acutatum fungal colonies by 64.17% when compared to control at 6 days after inoculation.